Priority Program of Unemployment Problem Solving in Pati Regency - Erni Arivia Roseline; Sucihatiningsih D.W.P (Economics Development Department, Universitas Negeri Semarang, Indonesia, 2016)
Pati is one regency that has the population with labor problems that is unemployment, and in 2013 Pati is a regency / city in Central Java with the fourth rank of unemployment rate. This research aims to make some program alternatives and to determine which alternative program that can be prioritized by the Government of Pati Regency in reducing the unemployment rate. The research uses the primary and secondary data. The analytical method used is Analysis Hierarchy Process (AHP) and it is processed using the expert choice version 9.0. The result of research indicates that the efforts to reduce the unemployment rate in Pati Regency can be prioritized on the criterion: (1) empowering the people, and followed by (2) the capital from the investors, and (3) the empowerment of economic business. And the priority scale from the entire program alternatives of unemployment problem solving is a program to improve the rural community empowerment. The advice that can be given from this research is that the Government of Pati Regency should continuously conduct the job training and coaching to improve the quality and skills of the labors and also should increase the job opportunities, and also should improve and perform the continuous improvement program of increasing the community empowerment so that the rural communities may have good quality to be able to compete with other labors.